The performance of dry spell-based index to predict agricultural drought. Issue 1 (1st December 2022) - Ferijal, T; Subhan
Abstract: This study was intended to analyze dry spell-based drought index (SDI) performance in predicting agricultural drought. Agricultural drought was estimated using soil moisture deficit index (SMDI) over a monthly time-scale. The deficit in soil moisture was calculated using soil water content in soil profile predicted by SWAT model. The result indicated that SDI has poor performance in predicting agricultural drought index. However, the outcome might be explained by the low temporal resolution of soil moisture data.